Fabrication of carbon thin films by pulsed laser deposition in different ambient environments - Abd. Mubin, M. H. (Penerbit UTM Press, 2016)
In this work, carbon thin films are grown in different background environments (Air, Helium and Argon) at different pressures (60, 160, 500 and 1000 mbar) by ablating the graphite target with Nd:YAG laser of wavelength of 1064 nm, pulse energy of 740 mJ and pulse rate of 6 ns. 10,000 laser shots are used to ablate graphite target under different ambient conditions. Grown thin films are analyzed by Atomic Force Microscopy (AFM) to measure thickness, roughness average, maximum profile peak height, average maximum height of profile and spacing ratio of the surface. The obtained results show that the roughness average, thickness of film, maximum profile peak height, average maximum height of profile and spacing ratio of thin films decreases with increase in ambient pressures and shows highest value at low pressure (160 mbar) in helium environment as compared with air and argon.